2013
DOI: 10.1007/978-1-4614-8289-5_6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Gadd45 Family in the Nervous System: A Focus on Neurodevelopment, Neuronal Injury, and Cognitive Neuroepigenetics

Abstract: The growth arrest and DNA damage-inducible (Gadd)45 proteins have been associated with numerous cellular mechanisms including cell-cycle control, DNA damage sensation and repair, genotoxic stress, neoplasia, and molecular epigenetics. The genes were originally identified in in vitro screens of irradiation- and interleukin-induced transcription and have since been implicated in a host of normal and aberrant central nervous system processes. These include early and postnatal development, injury, cancer, memory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 163 publications
1
38
0
Order By: Relevance
“…Although contextual fear conditioning rapidly increases hippocampal Gadd45b mRNA levels in mice (Leach et al, 2012; Sultan et al, 2012), Gadd45b knockout has been reported to both impair (Leach et al, 2012) and enhance (Sultan et al, 2012) hippocampal-dependent memory. Nevertheless, these data support some involvement of DNA demethylation in hippocampal plasticity and memory (Sultan and Sweatt, 2013). …”
Section: Epigenetic Regulation Of Hippocampal Memorysupporting
confidence: 54%
“…Although contextual fear conditioning rapidly increases hippocampal Gadd45b mRNA levels in mice (Leach et al, 2012; Sultan et al, 2012), Gadd45b knockout has been reported to both impair (Leach et al, 2012) and enhance (Sultan et al, 2012) hippocampal-dependent memory. Nevertheless, these data support some involvement of DNA demethylation in hippocampal plasticity and memory (Sultan and Sweatt, 2013). …”
Section: Epigenetic Regulation Of Hippocampal Memorysupporting
confidence: 54%
“…These GR-induced local effects could explain some of the DNA methylation changes in response to stress exposure and similar mechanisms of local demethylation have been reported with other nuclear receptors (estrogen) and transcription factors [34][35][36]. Several mechanisms have been proposed for this transcription factor guided active demethylation and involve protein-protein interactions with methyl-DNA binding proteins and DNA repair mechanisms as well as an intermediate introduction of hydroxymethylation marks [37][38][39][40].…”
Section: Specific Versus Global Changesmentioning
confidence: 76%
“…Activation of the growth arrest and DNA damage 45 (Gadd45) gene family was also suppressed after ischemia in SUMO-KD mice. All 3 members of this gene family – Gadd45a, Gadd45b, and Gadd45g – have been identified as ischemia-regulated genes and they may play a protective role in brain ischemia injury (Chen et al, 1998; Sultan and Sweatt, 2013). …”
Section: Discussionmentioning
confidence: 99%